The Educational Systemin TheUK : Characteristics and Distinctiveness - MESSAOUDI, Chaima (University of Eloued جامعة الوادي, 2024)
يهدف هذا البحث إلى الكشف عنا لخصائص والسمات المميزة للنظام التعليمي في المملكة المتحدة من خلال معالجة سؤالين أساسيين: لأول يبحث عن الخصائص الأساسية التي يقوم عليها النظام التعليمي في المملكة المتحدة، بينما يستفسر الثاني عن السياسات والصالحات التعليمية المعاصرة في تميزه. باستخدام التحليل النوعي والوصفي، تستكشف الدراسة التعقيدات الهيكلية، والمناهج المتنوعة، وطرق التقييم، ونماذج الحكومة، وتأثير انتقال السلطة على الاختلافات الإقليمية. تؤكد النتائج على نظام متعدد المستويات يشمل التعليم الابتدائي والثانوي والعالي والتعليم الإضافي، مما يعكس القدرة على التكيف والديناميكية. تكشف المناهج الوطنية عن مناهج تربوية متنوعة، مدعومة بأساليب تقييم شاملة. يؤثر انتقال السلطة على ا لفوارق الإقليمية في تصميم مما يسلط الضوء على نظام متجاوب. تظهر المدارس المتخصصة والسياسات، المناهج وطرقا لتقييم والوصول العادل للتعليم العالي وضمان الجودة الالتزام بالتعليم الفردي والمعايير الصارمة. تسود الروح التي تتمحور حول الطالب، مما يدل على التفاني في التعليم الجيد. This research aims to reveal the characteristics and distinctive attributes of the United Kingdom's educational system by addressing two core questions: The first seeks the fundamental characteristics underpinning the UK's educational system while the second inquiries about contemporary educational policies and reforms contribute to its distinctiveness. Employing qualitative and descriptive analysis, the study explores structural intricacies, diverse curricula, assessment methods, governance models, and the impact of devolution on regional variations. Findings underscore a multi-tiered system encompassing primary, secondary, higher, and further education, reflecting adaptability and dynamism. National curricula reveal diverse pedagogical approaches, supported by comprehensive assessment methods. Devolution influences regional disparities in curriculum design, assessment methods, and policies, highlighting a responsive system.Specialized schools,equitable higher education access,and quality assurance emonstrate commitment to individualized education and rigorous standards. The student-centered ethos pervades, showcasing dedication to quality education.
Literature and Civilization
Keywords: النظام التعليمي، المملكة المتحدة البريطانية، خصائص، تميز; Educational System; United Kingdom; Characteristics; Distinctiveness.